2020
DOI: 10.1680/jmacr.18.00279
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical-based design of hybrid steel fibre-reinforced concrete tunnels

Abstract: Hybrid steel fibre-reinforced concrete (HSFRC) composites, constituted from different geometries of steel fibres, benefit from positive performances of different fibre geometries. When applied in segmental tunnels, different aspects of their structural performance should be adequately evaluated to ensure a safe and durable design. In this paper, the flexural behaviour of segmental joints and performance under tunnel-boring machine (TBM) thrust forces for HSFRC segments is separately investigated through an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, the high-performance concrete has been gradually applied as shotcrete in building the tunnel lining for enhancing the tunnel performance in recent years [14][15][16]. The fiber-reinforced concrete (FRC) is adopted in tunnel lining for increasing the stability and bearing capacity of surrounding rocks [17][18][19], the functional cementitious composite (FCC) and fiberreinforced plastics (FRP) are utilized to increase the deformation ability and damage tolerance of lining structure [20][21][22], and steel plate is used for resisting the explosion impact on tunnel lining [23]. This application of the high-performance materials provides the opportunity of developing new-type lining structure without the shortages in the aforementioned composite lining structure, in which the single-layer tunnel lining using shotcrete is developed for supporting the tunnel construction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high-performance concrete has been gradually applied as shotcrete in building the tunnel lining for enhancing the tunnel performance in recent years [14][15][16]. The fiber-reinforced concrete (FRC) is adopted in tunnel lining for increasing the stability and bearing capacity of surrounding rocks [17][18][19], the functional cementitious composite (FCC) and fiberreinforced plastics (FRP) are utilized to increase the deformation ability and damage tolerance of lining structure [20][21][22], and steel plate is used for resisting the explosion impact on tunnel lining [23]. This application of the high-performance materials provides the opportunity of developing new-type lining structure without the shortages in the aforementioned composite lining structure, in which the single-layer tunnel lining using shotcrete is developed for supporting the tunnel construction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Steel FRC (SFRC) segments, has been investigated in various research efforts [12][13][14] and practiced in numerous projects worldwide [14]. It has been shown that fibers improve both structural [15][16][17] and durability [18] of the segmental tunnel. Studies on the performance of FRC tunnels are mainly focused on loading conditions normally experienced from the tunnel assembly phase (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on hybrid composites were mainly focused on cement paste or mortar. However, research on developing exact proportions and methods for combining various fibers to produce and maximize synergistic response is on the agenda [17,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The idea to use fibers as the main reinforcement mechanism in replacement of reinforcing bars in concrete segmental tunnels has been investigated in various research efforts [7][8][9] and practiced in numerous projects worldwide [9]. It has been shown that fibers improve both structural [10][11][12] and durability [13] of the segmental tunnel. Studies on the performance of FRC tunnels are mainly focused on loading conditions normally experienced from the tunnel assembly phase (e.g.…”
mentioning
confidence: 99%
“…They initially conducted an experimental program to characterize various SFRC composites and obtain their mechanical properties. A macro and micro steel fiber was used to produce both hybrid [12,19,20] and non-hybrid SFRC mixes. The mechanical properties of the SFRC composites to develop a soil-tunnel finite element model.…”
mentioning
confidence: 99%